Review of the genus Dopasia Gray, 1853 (Squamata: Anguidae) in the Indochina subregion - Nguyen, Truong Quang; Böhme, Wolfgang; Nguyen, Tao Thien; Le, Quyet Khac; Pahl, Kristian Robert; Haus, Tanja; Ziegler, Thomas (Zootaxa, 2011)
A review of the genus Dopasia Gray, 1853 in the Indochina subregion is provided with the first country record of D. hainanensis for Vietnam and new distribution records for other species. In addition, we herein confirm the validity of Dopasia ludovici, previously a synonym of D. harti, based on overlooked external morphological differences.